ABOUT POWER FACTOR AND THDI IN THE SMART MICRO-GRID SCENARIO - Pomilio, Jose A.; Bonaldo, Jakson P.; Morales-Paredes, Helmo K. [UNESP]; Tenti, Paolo; IEEE (Ieee, 2015)
This paper discusses the necessity of reviewing some traditional quantities used for qualifying electrical load properties. In the scenario of smart microgrids and distributed generation, the use of relative quantities, as the power factor and the current total harmonic distortion, can lead to the misinterpretation of the load behavior. The article presents some numeric examples and demonstrates the wrong conclusions that can derive from the use of such quantities especially in case of an consumer unity that is also an energy producer, what leads to the importance of reviewing some electricity standards and codes.
Keywords: Distributed Generation; Power Factor; Smart-Grid; Total Harmonic Distortion